2020
DOI: 10.1111/srt.12800
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of changes in cutaneous carotenoids after chemotherapy using shifted excitation resonance Raman difference and fluorescence spectroscopy

Abstract: Background Various cutaneous toxicities under chemotherapy indicate a local effect of chemotherapy by secretion after systemic application. Here, changes in the fluorescence and Raman spectral properties of the stratum corneum subsequent to intravenous chemotherapy were assessed. Methods Twenty healthy subjects and 20 cancer patients undergoing chemotherapy were included. Measurement time points in cancer patients were before the first cycle of chemotherapy (Tbase) and immediately after intravenous application… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In a pilot study of 20 patients that were suffering from various cancers, it was shown that the concentration of carotenoids in the SC of patients that were measured before chemotherapy was significantly lower than that of healthy individuals ( p < 0.001) [ 219 ], probably due to the psychological burden and anxiety that cancer patients suffered from or the accumulating long-lasting effect of previous chemotherapy cycles [ 220 ]. Although the concentration of carotenoids in the SC does not correlate with the age of a healthy person [ 192 ], such a correlation has been found for the skin of patients suffering from cancer, which was decreasing with increasing patient age [ 221 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%
See 3 more Smart Citations
“…In a pilot study of 20 patients that were suffering from various cancers, it was shown that the concentration of carotenoids in the SC of patients that were measured before chemotherapy was significantly lower than that of healthy individuals ( p < 0.001) [ 219 ], probably due to the psychological burden and anxiety that cancer patients suffered from or the accumulating long-lasting effect of previous chemotherapy cycles [ 220 ]. Although the concentration of carotenoids in the SC does not correlate with the age of a healthy person [ 192 ], such a correlation has been found for the skin of patients suffering from cancer, which was decreasing with increasing patient age [ 221 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%
“…The fluorescent signal of doxorubicine could be detected 1–2 h after starting the intravenous infusion and remained there for at least 4.5 h [ 223 ] until it disappeared. Other non-fluorescent drugs, such as paclitaxel, 5-fluorouracil, and folinic acid, despite the presence of specific Raman bands [ 224 ], could not be detected on the skin surface in vivo by CRM, which may be due to their chemical properties, low concentration, and/or metabolism [ 219 ]. Before the invention of targeted therapies and immune therapy, many common chemotherapeutic agents were based on or caused radical formation, e.g., cytostatics inducing in particular ROS, increasing the amount of oxidation products in the body [ 225 , 226 ].…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%
See 2 more Smart Citations
“…17). Also, here results from measurements in the frame of a clinical study [14,15] and a nutrition study were published [16]. The necessary software for system control, data management, and data analysis was developed by FBH.…”
Section: Systems and Applicationsmentioning
confidence: 99%